Educating Greek Americans Historical Perspectives and Contemporary Pathways - Soumakis, Fevronia K.; Zervas, Theodore G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This edited collection considers Greek American formal and informal educational efforts, institutions, and programs, broadly conceived, as they evolved over time throughout the United States. The book$1 (Bs focus on Greek Americans aims to highlight the vast array of educational responses to local needs and contexts as this distinct, yet, heterogeneous immigrant community sought to maintain its linguistic, cultural, and religious heritage for over one hundred years. The chapters in this volume amend the scholarly literature that thus far has not only overlooked Greek American educational initiatives, but has also neglected to recognize and analyze the community$1 (Bs persistence in sustaining them. This book is an important contribution to an understanding of Greek Americans$1 (Blong overdue history as a significant diaspora community within an American context.s
1. Introduction: Educating Greek Americans -- 2. Greek Orthodox Education: Challenges and Adaptations in New York City Schools -- 3. The First Educational Books for Greek Children in America -- 4. Considering the "Socratic Method" When Teaching he Odyssey and Iliad at the Socrates and Koraes Greek American Schools -- 5. Breaking the Traditional Greek School Mold: The Case of the Aristotle GSL Program -- 6. An American and Greek Language Integrated Curriculum for A Dual Language Immersion Program: The Case of Odyssey Charter School -- 7. Promoting Heritage, Ethnicity, and Cultural Identity in Diasporic Communities: The Case of the Heritage Greece Program -- 8. Conclusion: When We Were Greek.
Keywords: Educational sociology; Emigration and immigration; Church and education; Language and education; Orthodox Eastern Church; Ethnicity in Education; Diaspora; Religion and Education; Language Education; Eastern Orthodoxy